Solid Solution Effects on the Thermal Properties in the MgAl2O4–MgGa2O4 System. Issue 3 (24th December 2012) - Wilkerson, K. R.; Smith, J. D.; Sander, T. P.; Hemrick, J. G.
Abstract : Solid solution effects on thermal conductivity within the MgO–Al2 O3 –Ga2 O3 system were studied. Samples with systematically varied additions of MgGa2 O4 –MgAl2 O4 were prepared and the laser flash technique was used to determine thermal diffusivity at temperatures between 200°C and 1300°C. Heat capacity as a function of temperature from room temperature to 800°C was also determined using differential scanning calorimetry (DSC). Solid solution in the MgAl2 O4 –MgGa2 O4 system decreases the thermal conductivity up to 1000°C. At 200°C thermal conductivity decreased 24% with a 5 mol% addition of MgGa2 O4 to the system. At 1000°C, the thermal conductivity decreased 13% with a 5 mol% addition. Steady‐state calculations showed a 12.5% decrease in heat flux with 5 mol% MgGa2 O4 considered across a 12 inch thickness.